Rational Design of Smart Hydrogels for Biomedical Applications - Zhang, Yanyu; Huang, Yishun (Frontiers in Chemistry, 2021)
Hydrogels are polymeric three-dimensional network structures with high water content. Due to their superior biocompatibility and low toxicity, hydrogels play a significant role in the biomedical fields. Hydrogels are categorized by the composition from natural polymers to synthetic polymers. To meet the complicated situation in the biomedical applications, suitable host-guest supramolecular interactions are rationally selected. This review will have an introduction of hydrogel classification based on the formulation molecules, and then a discussion over the rational design of the intelligent hydrogel to the external stimuli such as temperature, pH, light and targeted biomolecules. Further, the applications of rationally designed smart hydrogels in the biomedical field will be presented, such as tissue repair, drug delivery and cancer therapy. Finally, the perspectives and the challenges of smart hydrogels will be outlined.